Exploration of knowledge management system for sustainable community-based tourism development : case study of Bang Rong, Phuket Province - Phanaranan Sontiwanich (Prince of Songkla University, 2016)
Thesis (M.Sc. (Environmental Management Technology))--Prince of Songkla University, 2015